2022
DOI: 10.22146/ijbiotech.67506
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of KRAS and BRAF mutation in colorectal cancer patients in Bali

Abstract: Mutations in the KRAS (Kirsten rat sarcoma viral oncogene homolog gene) and BRAF (v‐Raf murine sarcoma viral oncogene homolog B1) gene play a significant role in primary resistance to colorectal cancer therapy. Around 85‐90% of KRAS mutations in colorectal cancer occur in exon 2 (codon 12 and 13), whereas approximately 96% of BRAF mutations occur in exon 15 codon 600 (V600E). This study aimed to determine the prevalence and mutation characteristics of the KRAS and BRAF genes in colorectal cancer patients in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The tumour was found in the cecum colon, descending colon, sigmoid colon, and rectum (Table 1). Previous research in Indonesia found that the incidence of colorectal cancer was higher in people over 50 (Indrayani M & Sriwidyani, 2017;Ni Nyoman et al, 2022;Saleh et al, 2019). Molenaar et al reported that 90% of CRC occurs at ages above 50.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The tumour was found in the cecum colon, descending colon, sigmoid colon, and rectum (Table 1). Previous research in Indonesia found that the incidence of colorectal cancer was higher in people over 50 (Indrayani M & Sriwidyani, 2017;Ni Nyoman et al, 2022;Saleh et al, 2019). Molenaar et al reported that 90% of CRC occurs at ages above 50.…”
Section: Resultsmentioning
confidence: 98%
“…In Bali, males were more likely to develop colorectal cancer, and the risk increased with age. KRAS mutations in exon two have been identified, with G13D being the most common, followed by G12D and G12V (Ni Nyoman et al, 2022). In West Java people, KRAS and p53 mutations are involved in carcinogenesis and have a significant association between KRAS gene expression and p53 immuno-expressions in colorectal adenocarcinoma KRAS (Rachmawati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the status and exact mechanisms are still unclear, a high prevalence status may indicate a new treatment area exploration concerning this specific mutation. Previously, the BRAF V600E mutation focused on malignant tumours, where the prevalence was approximately 74.6% for papillary thyroid carcinoma [ 95 ], 7.4% for colorectal cancer [ 96 ], and 60% for melanomas [ 97 ]. According to previous studies, several gene mutations have been identified in the background of BRAF V600E positive mutation in ameloblastoma, including somatic mutation in cyclin-dependent kinase inhibitor 2A ( CDKN2A ), catenin beta 1 ( CTNNB1 ), fibroblast growth factor receptors ( FGFR ), Kirsten rat sarcoma virus ( KRAS ), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha ( PIK3CA ), and phosphatase and tensin homolog ( PTEN ) [ 19 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CIMP, which is characterized by CG dinucleotide methylation in the promoters of numerous genes, is associated with distinct clinical and pathological attributes in tumors. These subtypes, as described by Jass Classification, include CIMP high/MSI high (12% of CRC), CIMP low/MSI low or microsatellite stable (20%), CIMP negative/microsatellite stable (57%), and Hereditary Non Polyposis Colorectal Cancer (HNPCC), with CIMP negative/MSI high and negative for BRAF mutations [7,[9][10][11][12]. Testing for MSI and MMR protein deficiency is commonly the first step in LS diagnostics due to germline mutations of MMR genes.…”
Section: Introductionmentioning
confidence: 99%